A Cross-Temporal Meta-Analysis on Marital Satisfaction of Chinese Couples - Li, Fengzhan; Chen, Chen; Wang, Jinrui; Peng, Haiyun; Wu, Lin; Ren, Lei; Song, Lei; Jin, Yinchuan; Yang, Qun (Frontiers in Psychology, 2022)
Objective To investigate the changing trend of Chinese couples' marital satisfaction and its relationship with social changes. Methods A cross-temporal meta-analysis was performed on 118 original studies (n = 31,909) reporting marital satisfaction of Chinese couples from 1994 to 2020, primarily using correlation analysis and regression analysis. Results (1) Overall, the marital satisfaction of Chinese couples showed a downward trend over time. (2) Men's marital satisfaction displayed almost no change, while women's marital satisfaction had a more obvious downward trend. (3) Changes in macrosocial factors (per capita consumption expenditure, housing prices, old-age dependency ratio, and divorce rate) could significantly predict the downward trend of marital satisfaction, especially for women. Conclusion In the past 27 years, the overall marital satisfaction level of Chinese couples has shown a downward trend, and there are gendered differences, which may be related to changes in the socioeconomic and cultural environments.